1996
DOI: 10.1021/la9502958
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Perfluorodiethyl Ether and Diethyl Ether on the TiO2 Surface

Abstract: The adsorption and thermal decomposition of a perfluorinated ether and an alkyl ether have been studied on the TiO2 surface using Fourier transform infrared spectroscopy. It has been found that the fully fluorinated ether, (C2F5)2O, physisorbed onto the TiO2 surface. As the surface was heated to 500 K, it was found that the (C2F5)2O thermally decomposed to a surface fluoroacetate species at temperatures greater than 200 K. The more acidic surface hydroxyl groups are permanently perturbed by the oxidation react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…They did not propose a clear mechanism for this conversion but they corroborated the importance of acidic OH on the surface for this to occur. Their results for (C 2 F 5 ) 2 O and DEE adsorbed on TiO 2 [34] show mostly formation of ethoxides on the surface in the case of DEE, and mostly fluoroacetates for (C 2 F 5 ) 2 O but the formation of fluoroformates is not seen as was the case on Al 2 O 3 . On SiO 2 [32] they found that the ether molecules strongly interact with the hydroxyls on the surface but no decomposition products were detected.…”
Section: Diethyl Ether On Hydroxylated Ceox By S-xpsmentioning
confidence: 92%
See 1 more Smart Citation
“…They did not propose a clear mechanism for this conversion but they corroborated the importance of acidic OH on the surface for this to occur. Their results for (C 2 F 5 ) 2 O and DEE adsorbed on TiO 2 [34] show mostly formation of ethoxides on the surface in the case of DEE, and mostly fluoroacetates for (C 2 F 5 ) 2 O but the formation of fluoroformates is not seen as was the case on Al 2 O 3 . On SiO 2 [32] they found that the ether molecules strongly interact with the hydroxyls on the surface but no decomposition products were detected.…”
Section: Diethyl Ether On Hydroxylated Ceox By S-xpsmentioning
confidence: 92%
“…Further explanation on these controversial results stated that probably the different experimental conditions and preparation of the high surface area catalysts were responsible for the different results obtained. [26] Alkyl ethers have also been of interest due to their role as lubricants leading to studies to elucidate the reactivity of alkyl and perfluoro-alkyl ethers on metals [27][28][29][30][31] and on oxides [13,14,[32][33][34][35][36][37][38][39]. It is interesting to note that several of these studies showed reaction of the ethers adsorbed on the oxides (Al 2 O 3 , SiO 2 , TiO 2 and ZrO 2 ) to form alkoxides, potentially due to the presence of hydroxyls and also further conversion of these alkoxides to carboxylates.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results published by our group of IR spectra of reactions of fluorinated ethers with alumina and titania surfaces [3,7], we attribute the newly formed features at 1442 cm À1 and 1606 cm À1 to the symmetric and antisymmetric OCO stretch of fluorinated formate, the features at 1479 cm À1 and 1678 cm À1 to the symmetric and antisymmetric OCO stretch of fluorinated acetate and 1345 cm À1 and 1606 cm À1 to the symmetric and antisymmetric OCO stretch of alkyl formate. These assignments as well as the data they are based upon are summarized in Table 1.…”
Section: Thermal Reaction Of 222-trifluoroethanol On the Alumina Sumentioning
confidence: 82%
“…New peaks appeared at 1618 and 1680 cm À1 at 400 K, and their intensities increased significantly by 500 K. The band at 1457 cm À1 decreased until 350 K and then increased at 450-500 K. These features are assigned to the symmetric and asymmetric stretching modes of surface fluorinated carboxylates. The assignments are made based on published assignments of fluorinated carboxylates on alumina Table 1 The observed vibrational frequencies of physisorbed and gas phase difluoroethanol, in wavenumbers (cm À1 ), at different temperatures [3,[9][10][11]14,16,22,23]. Assignment of the observed vibrational modes of the reaction products are summarized in Table 2.…”
Section: Effect Of Thermal Treatment Of Cf 2 H-ch 2 -Oh On Al 2 Omentioning
confidence: 99%